Direct Synthesis of Ammonia from N2 and H2O on Different Iron Species Supported on Carbon Nanotubes using a Gas‐Phase Electrocatalytic Flow Reactor. Issue 14 (13th May 2020) - Chen, Shiming; Perathoner, Siglinda; Ampelli, Claudio; Wei, Hua; Abate, Salvatore; Zhang, Bingsen; Centi, Gabriele
Abstract: Green NH3 production by direct electrocatalytic synthesis from N2 and H2 O is still a challenging reaction, which requires us to better understand the nature of the active materials. We show here that iron oxide (Fe2 O3 ) nanoparticles (supported over carbon nanotubes, CNTs) become more active than the corresponding samples after reduction to form Fe‐ or Fe2 N‐supported nanoparticles, both indicated as active species in the thermal catalytic reduction of N2 to ammonia. Characterization data, however, indicate that even for these Fe‐ and Fe2 N−CNT samples, obtained from Fe2 O3 −CNT by reduction in H2 or NH3 at 500 °C, the active species responsible for N2 reduction reaction (NRR) at low applied potential (−0.5 V vs RHE) are the same, that is, small (<1–2 nm) iron oxide nanoparticles that are not detected by XRD, but evidenced by XPS and which amount could be correlated to the rate of ammonia formation. This species is stable for at least 24 h of electrocatalytic flow tests. However, at higher applied potentials, sintering/transformation of this species occurs, with loss of the electrocatalytic activity, and Fe2 N nanoparticles may also be reduced in situ, forming ammonia, but with irreversible deactivation. Abstract : Go with the flow : Small (<1–2 nm) iron‐oxide nanoparticles strongly interacting with carbon nanotubes are the active species responsible for the N2 reduction reaction (NRR) at low applied potential (−0.5 V vs RHE).